2015
DOI: 10.1115/1.4031260
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation on the Characteristics of Turbulent Boundary Layer Flows Over a Dimpled Surface

Abstract: An experimental investigation was conducted to quantify the characteristics of the turbulent boundary layer flows over a dimpled surface in comparison to those over a conventional flat plate. In addition to measuring surface pressure distributions to determine the friction factors of the test plates and to map the surface pressure inside the dimple cavity, a high-resolution digital particle image velocimetry (PIV) system was used to achieve detailed flow field measurements to quantify the characteristics of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…The parameters of the surface relief do not influence this specifically or immediately since they do not prescribe the vortex structures to deviate in a coordinated fashion in one or the other direction. The matching of states is due to nonlinearity of the equations of motion of the continuous medium, which also manifests itself when large-scale vortex structures [19,20] arise.…”
Section: Reviewmentioning
confidence: 99%
“…The parameters of the surface relief do not influence this specifically or immediately since they do not prescribe the vortex structures to deviate in a coordinated fashion in one or the other direction. The matching of states is due to nonlinearity of the equations of motion of the continuous medium, which also manifests itself when large-scale vortex structures [19,20] arise.…”
Section: Reviewmentioning
confidence: 99%
“…After passing through the pin fin, part of the airflow nearby the dimple separates and is involved in the flow recirculation at the front half of the dimple where a relatively lower TKE region is born, which will be discussed later. The remaining airflow shifts downwards by the flow recirculation and impinges on the rear half of the dimple [38]. The impingement on the rear half of the dimple can make the boundary layer thinner and this is remarkably beneficial for the heat transfer augmentation.…”
Section: Definition Of Parametersmentioning
confidence: 99%
“…Li et al (2018) conducted a numerical study on the heat transfer performance of water-cooled micro channel radiators with protrusion and pin-fins, and further optimized them. Zhou et al (2016) investigated experimentally the flow characteristics of turbulent boundary layer flows over a convex and flat plate surface. The results showed that the flow characteristics of turbulent boundary layer over the convex surface were much more complex, especially in the region near the back rims of the protrusion.…”
Section: Introductionmentioning
confidence: 99%